4‐(4‐Bromophenyl)thiazol‐2‐amine: Crystal structure determination, DFT calculations, visualizing intermolecular interactions using Hirshfeld surface analysis, and DNA binding studies. (7th May 2019) - Channar, Pervaiz A.; Arshad, Nasima; Larik, Fayaz A.; Farooqi, Shahid I.; Saeed, Aamer; Hökelek, Tuncer; Batool, Bakhtawar; Ujan, Rabail; Ali, Hafiz Saqib; Flörke, Ulrich
Abstract: 2‐Aminothiazole is a valuable synthon in organic synthesis and an important structural unit of pharmaceutically active drugs. It is accessible via several synthetic routes. In the current account, compound4 {4‐(4‐bromophenyl) thiazol‐2‐amine} was synthesized by employing a recently reported procedure of Gabriel synthesis using Lawesson reagent. The title compound was characterized through spectro‐elemental analytical data, and its crystal structure was determined by single‐crystal X‐ray diffraction. The torsion angles, bond lengths, and bond strengths between the planes of the thiazole and phenyl rings were optimized by theoretical calculations by applying the B3LYP/6‐311++G(d, p) level for the purpose of investigating the conformational effects on the stabilization of the crystal packing. HOMO‐LUMO analysis, vibrational analysis, and thermodynamic parameters were also investigated. A detailed analysis of the intermolecular interactions of thiazole moiety bearing the amino and bromophenyl ring has been performed based on the Hirshfeld surfaces and their associated two‐dimensional fingerprint plots. The relative contributions of the main intermolecular contacts as well as the enrichment ratios derived from the Hirshfeld surface analysis establish the 2‐aminothiazole synthon to be a molecule of great interest. DNA binding studies pointed towards anticancer potency of the synthesized compound via reversible binding. Abstract : 4‐(4‐bromophenyl)thiazol‐2‐amine is reported for synthesis, characterization, crystal structure, computational, and Hirshfeld surface analysis. DNA binding studies pointed towards anticancer potency of the synthesized compound via reversible intercalative binding.